CINNAMOSMA MACROCARPA AND ITS FRACTIONS ARE ACTIVE IN VITRO AGAINST BETANODAVIRUS - Galligioni, V.; Vaccari, F.; Galletti, E.; Matera, R.; Fontana, G.; Ciulli, S.; Scagliarini, A. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Betanodavirus is the causative agent of viral encephalopathy and retinopathy (VER). VER is considered one of the most serious viral diseases in aquaculture causing enormous losses in species of high economic value as sea bass and halibut (1). No commercial vaccine is available and the most efficacious countermeasures against VER are the traditional prophylactic methods (2). Cinnamosma is widely used in traditional medicine and it’s active in vitro against several viruses (3). In this study we evaluated the in vitro efficacy of the essential oil of Cinnamosma macrocarpa against Betanodavirus. The cytotoxicity (CC50) of the oil was determined on SSN-1 cells comparing treated cells with untreated control cells by coulter counter and the antiviral activity (IC50) by the cytopathic effect inhibition assay. The selectivity index (SI) was calculated as the ratio of CC50 and IC50. Due to the efficacy exhibited by Cinnamosma oil, 7 fractions obtained from column chromatography with different degree of polarity were tested to identify the fraction of the oil responsible for the antiviral activity. Three fractions showed intracellular antiviral activity with values ranging from 21 mg/ml to 54 mg/ml and cytotoxicity between 100 mg/ml and 200 mg/ml. The SI varied from 3 to 4.8. The most polar extracts were the most effective. Cinnamosma oil and its polar fractions were active against the in vitro replication of Betanodavirus. Further studies are needed to elucidate the mechanism of action and to investigate the efficacy of Cinnamosma derivatives in vivo as a possible candidate to treat VER disease.References:1-Samuelsen O., Nerland AH., Jorgensen T., Schroder MB., Svasand T., Bergh O. (2006). Dis. Aquat. Organ. 71(3):239-54. 2-Harinantenaina L., Yoshinori A., De Clerq E. (2007). J. Nat. Prod. 70, 277-28